AESTHETIC INTELLIGENCE IN COCA-COLA’S 2024 ‘CREATE REAL MAGIC’ CAMPAIGN: GENERATIVE AI AND VISUAL STORYTELLING - I Gusti Agung Rangga Lawe (Telkom University, 2026)
This study examines how Coca-Cola, a big brand long associated with emotional storytelling, used generative artificial intelligence (AI) in its 2024 “Create Real Magic” campaign. Unlike the company’s traditional nostalgic advertisements, the campaign introduced three AI-generated Christmas ads, “Unexpected Santa,” “Secret Santa,” and “Silver Santa,” that featured surreal imagery and experimental storylines. A qualitative case study design was applied, drawing on secondary data from official campaign materials, media coverage, the three advertisements, and YouTube audience comments. The analysis focused on visual themes, symbolic elements, and audience responses. The findings reveal a clear shift from Coca-Cola’s warm, human-centered narratives. The AIdriven ads enabled faster production and creative experimentation but weakened authenticity and emotional depth. Audience reactions were sharply divided, while some praised the innovation, others criticized the ads as “creepy,” “soulless,” or inconsistent with Coca-Cola’s holiday traditions. These polarized responses reflect both the creative opportunities of generative AI and wider ethical concerns over authenticity and trust in advertising. The novelty of this research lies in its focus on a globally famous brand’s direct use of generative AI in mainstream advertising. The study concludes that while AI expands creative horizons, big brands risk alienating audiences if innovation overshadows emotional connection. Limitations include reliance on secondary data and the absence of performance metrics such as demographic reach or engagement rates. Future research could address these gaps through focus group discussions, A/B testing, or multimodal analysis to offer more details about consumer responses to AI-driven advertising